Perlindungan Sosial Bagi Perempuan Korban Pernikahan Dini di Gorontalo - Yuhelson, Yuhelson; Lina Sinaulan, Ramlani; Rahmat, Abdul (UIN Sunan Kalijaga, Yogyakarta, Indonesia, 2020)
This study explores the dynamic of early-age marriage and implementing social protection concepts for households’ women victims in Gorontalo. This research uses qualitative method with explorative-inductive approaches. We were collected data by interviews, observation, and documentation. Resulting studies that early-age marriage cases in Gorontalo effected by low education, patriarchy system, domestic violence, divorced, and multi-dimensional poverty. For that, this study recommended that social control be worked fine, where the role of parent’, education, and community—create a social safety net for getting better—this role of parents and educational institutions in implementing the protection concept as a social policy reformulation material.Studi ini mengeksplorasi dinamika pernikahan dini dan skema perlindungan sosial yang tepat bagi perempuan korban kekerasan dalam ruamh tangga di Gorontalo. Penelitian ini menggunakan metode kualitatif dengan pendekatan eksploratif-induktif. Data dikumpulkan dengan wawancara, observasi, dan dokumentasi. Hasil studi menunjukkan bahwa kasus pernikahan dini di Gorontalo disebabkan oleh rendahnya tingkat pendidikan, budaya patriarkhi, kekerasan dalam rumah tangga, perceraian, dan kemiskinan multidimensi. Untuk itu, studi ini merekomendasikan agar kontrol sosial dapat berfungsi dengan baik—peran orang tua, sekolah, dan komunitas—agar social safety net berjalan dengan baik. Peran ini tercermin dalam konsep perlindungan sebagai bahan untuk reformulasi kebijakan sosial.